Peningkatan Pengetahuan Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan tentang Stunting di Desa Marong, Kec. Praya Timur. Kab. Lombok Tengah, NTB - Sahrip, Sahrip; Fitria, Hidayatun; Huda, Haerul (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
In Indonesia, there are 1.2 million babies born with stunting. For this reason, in early 2021, the Indonesian Government targeted the Stunting rate to decrease to 14% in 2024. Central Lombok Regency, stunting cases in 2021 were 20.81%. This number makes Central Lombok Regency in the 5th position for the areas with the most stunting sufferers in NTB Province. From the distribution of stunting sufferers in Central Lombok Regency, in East Praya District, the number of stunting sufferers in 2021 was recorded at 745 children or 14% of the total number of toddlers of 5,276 children. Of the 10 villages in East Praya District, the village with the most stunting sufferers is Marong Village with 145 children out of 390 toddlers or 37%. The purpose of this PKM is to provide counseling and assistance to increase the insight and awareness of the people of Marong Village, Praya District, Central Lombok Regency in preventing and preventing stunting sufferers. The results achieved in this PKM are that participants' knowledge about handling and preventing stunting has increased. Where from the pre-test results with a very good level of knowledge reaching 53%, a good level of knowledge of 27% and a poor level of knowledge decreased to 20%.